Recruitment of pial collaterals and carotid occlusive disease in large-vessel occlusion ischemic stroke - Helwig, Niklas; Wagner, Marlies; Seiler, Alexander (Frontiers in Neurology, 2024)
Despite the fundamental role of pial collateral vessels in limiting the progression of ischemic tissue injury in acute stroke with large-vessel occlusion (LVO), besides the fact that collateral vessel abundance varies naturally from person to person for genetic reasons, there is limited knowledge regarding potential factors contributing to inherent interindividual variation in pial collateral supply.Since it has been repeatedly hypothesized that chronic carotid occlusive disease might favor pial collateralization, we aimed to investigate the association between quantitatively assessed leptomeningeal collateral supply and pre-existing carotid stenosis in patients with acute stroke due to LVO.Patients with proximal middle cerebral artery (MCA) occlusion with or without additional internal carotid artery (ICA) occlusion were included. The degree of collateral supply was quantitatively assessed based on signal variance in T2*-weighted time series in perfusion-weighted magnetic resonance imaging (MRI). Patients were stratified into two groups according to quantitative collateral status (poor and fair -good collateral supply). The prevalence of high-grade ICA stenosis (≥ 70 %) was evaluated in both groups.In this study employing quantitative and observer-independent MRI-based collateral assessment in patients with LVO, no significant difference in the prevalence of pre-existing high-grade ICA stenosis was found between patients with fair to good and patients with poor collateral supply. The potential influence of demographic and clinical variables on pial collateral supply in acute stroke patients warrants further exploration in future studies. MRI-based collateral supply is significantly related to initial stroke severity, ischemic core volume and early functional outcome.